Pengaruh Sektor Pariwisata Terhadap Pendapatan Asli daerah (PAD) di Kabupaten Sikka - Obiyanto Driantama Kause; Petrus Da Silva; Elisabet Luju (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2023)
Based on the formulation of the problem above, the researcher aims to determine the level of contribution of the tourism sector to regional own-source revenue (PAD) in Sikka regency. The population in this study was the Regional Revenue Agency (BAPENDA) and Tourism Department. The sample in this study was data on the target and realization of regional own-source revenue (PAD), as well as data on the target and realization of the tourism sector (hotel tax, restaurant tax and entertainment tax) in the Sikka Regency budget and expenditure relazation report (APBD) for fiscal year 2018-2022 and data on tourist visits in Sikka Regency for fiscal year 2018-2022. The t test results revealed that the hotel tax variabel (X1) and the entertainment tax variable (X2) had an insignificant effect on regional own-source revenue (Y) while the restaurant tax (X3) had a significant influence on regional original revenue (Y). The F test results showed that the hotel tax variable (X1), entertainment tax variable (X2), and restaurant tax (X3) had an insignificant influence on regional own-source revenue (Y). The results of the coefficient of determination of the correlation coefficient value (r) of 0.842, this value occurred between the coefficient interval 0.80-1.00, hence the level of relationship between the independent variables with regional own-source revenue (Y) was interpreted as “very strong”.